ANALYSIS OF FACTORS INFLUENCING INTENTION IN USING ACCOUNTING INFORMATION SYSTEMS FOR REVENUE AND ZAKAT MANAGEMENT BY MICRO, SMALL AND MEDIUM ENTERPRISES IN E-COMMERCE - Zaid, Zaid; Susilawati, Endang; Mukti, Zisca Marcellina; Pratondo, Katon; Al Bahy, Mahbub Pasca (UIN Sunan Gunung Djati Bandung, 2024)
Accounting information systems (AISs) have become indispensable enterprise management tools, serving as a vital resource for promoting administrative and financial processes, facilitating decision-making, and improving overall performance. Apart from business, AISs can also be developed as zakat for sharia. In this regard, AIS plays a role in calculating zakat, making zakat payment decisions, and assisting managers in zakat allocation. This function is very beneficial for business actors, especially MSME actors. The existence of AISs can make it easier for MSMEs to manage their revenue and zakat. So, MSMEs need to be able to adopt AISs. Unfortunately, research regarding the acceptability of AIS adoption for MSMEs has not yet been conducted. Therefore, this research examines the factors of acceptance of AISs by e-commerce actors from MSMEs. By using the elements in the Technology Acceptance Model (TAM), such as Perceived ease of use (PEU) and perceived usefulness (PU) through quantitative methods and Partial Least Square Structural Equation Model (PLS-SEM) analysis, the results of data analysis in this study show that the influence of PEU and PU on IUAISs is positive and significant. This shows that IUAISs are influenced by two main variables from TAM (PEU and PU). Based on the results, this study implies that MSMEs that successfully adopt Accounting Information Systems (AISs) for revenue and zakat management can improve their administrative and financial efficiency, emphasizing the importance of understanding the factors influencing AIS acceptance among MSMEs.